2013
DOI: 10.1039/c3lc50868d
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered bioluminescent magnetotactic bacteria as a powerful tool for chip-based whole-cell biosensors

Abstract: This paper describes the generation of genetically engineered bioluminescent magnetotactic bacteria (BL-MTB) and their integration into a microfluidic analytical device to create a portable toxicity detection system. Magnetospirillum gryphiswaldense strain MSR-1 was bioengineered to constitutively express a red-emitting click beetle luciferase whose bioluminescent signal is directly proportional to bacterial viability. The magnetic properties of these bacteria have been exploited as "natural actuators" to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…Bridle [3] Genetically engineering in complex lab on a chip designs Relationships to bioengineering and system performance Roda et al [19] Configuration and instrumentation Illustrates design variability Bidmanova et al [2] Cell-coating encapsulation Biocatalysis; tuning metabolic activity to the application Park et al [13] identified the significance of quenching mechanisms as related to polymer chemistry, and Fritzsche et al [6] have shown variable absorbance characteristics are a function of fluorophore concentration when using a fluorescent dye similar to this research. Reardon et al [16,18] have reviewed photoluminescence-based biosensor technology specific to environmental applications, and early research by Reardon et al [17] and Reardon and Bailey [15] reinforced the importance of identifying the metabolic state of cells during immobilization.…”
Section: Introductionmentioning
confidence: 83%
“…Bridle [3] Genetically engineering in complex lab on a chip designs Relationships to bioengineering and system performance Roda et al [19] Configuration and instrumentation Illustrates design variability Bidmanova et al [2] Cell-coating encapsulation Biocatalysis; tuning metabolic activity to the application Park et al [13] identified the significance of quenching mechanisms as related to polymer chemistry, and Fritzsche et al [6] have shown variable absorbance characteristics are a function of fluorophore concentration when using a fluorescent dye similar to this research. Reardon et al [16,18] have reviewed photoluminescence-based biosensor technology specific to environmental applications, and early research by Reardon et al [17] and Reardon and Bailey [15] reinforced the importance of identifying the metabolic state of cells during immobilization.…”
Section: Introductionmentioning
confidence: 83%
“…Because the microfluidic device makes it possible to detect very low concentrations of HMIs, the application of this approach may not be limited to the small volume of samples. In addition, we note that the microfluidic device and bacterial biosensors have remarkable potential to be a portable biosensor because not only can the microfluidic device be operated by hydrostatic heads without any external pumping system but also integrated with a portable CCD camera system (Roda et al, 2013) for fluorescent detection. It is obvious that the microbial biosensors can be synthetically engineered to produce stronger fluorescence signals in response to metal ions for enhanced sensitivity and selectivity (Wu et al, 2009).…”
Section: Potential Application Of the Microfluidic Device And Microbimentioning
confidence: 99%
“…Microfluidic platforms are increasingly being used for monitoring cell activity and provide an ideal platform for the implementation of whole-cell biosensors. Roda et al (2013) took advantage of the properties of magnetotactic bacteria, using microfluidics to move the cells between the incubation and detection areas of the chip where they were trapped by an array of neodymium-iron-boron magnets. However, the fluid flows generated within microfluidic systems can generate fluid shear stress (FSS).…”
Section: Microfluidic Applications Highlightsmentioning
confidence: 99%